Effect of intracerebroventricular injection of somatostatin or GABA on pain threshold and contents of GABA or somatostatin in rat brain - ZHENG Lu; LI Xi-cheng (Acta Pharmacologica Sinica; Vol 16, No 4 (July 1995): Acta Pharmacologica Sinica, 2016)
AIM: To study the interactive influence of somatostatin (Som) and GABA in the brain and its relation to the pain modulation. METHOD: Using radioimmunoassay, amino acid analyzer and measurement of pain threshold. RESULTS: Som 10 micrograms i.c.v. increased the pain threshold (from 4.2 +/- 0.2 to 7.0 +/- 1.1 s) of the rat, but reduced the content of GABA from 2.3 +/- 0.3 to 1.6 +/- 0.4 mumol g-1 in hippocampus and from 2.4 +/- 0.4 to 1.5 +/- 0.2 mmol kg-1 in brain stem. After depletion of the Som in brain by i.c.v. cysteamine (Cys, 600 micrograms), the content of GABA in hippocampus and brain stem was also reduced without modification of the pain threshold. GABA 1500 micrograms i.c.v. had no effect on the pain threshold, however, caused a decrease of Som content from 55 +/- 4 to 37 +/- 5 ng g-1 in hippocampus and from 84 +/- 4 to 55 +/- 6 ng g-1 in brain stem, which was blocked by bicuculline (10 micrograms). After reduced of the GABA content in brain by subcutaneous injection of isoniazid (300 mg kg-1), Som content of the hippocampus and rain stem was markedly elevated. CONCLUSION: Som and GABA inhibited each other, unrelated to their pain modulation.